Pulsed Wave Doppler Ultrasound Is Useful to Assess Vasomotor Response in Patients with Multiple System Atrophy and Well Correlated with Tilt Table Study - Ke-Vin Chang; Wen-Shiang Chen; Ruey-Meei Wu; Ssu-Yuan Chen; Hsiu-Yu Shen; Ching Lan; Yen-Ho Wang (The Scientific World Journal)
The study aim was to assess sympathetic vasomotor response (SVR) by using pulsed wave Doppler (PWD) ultrasound in patients with multiple system atrophy (MSA) and correlate with the tilt table study. We recruited 18 male patients and 10 healthy men as controls. The SVR of the radial artery was evaluated by PWD, using inspiratory cough as a provocative maneuver. The response to head-up tilt was studied by a tilt table with simultaneous heart rate and blood pressure recording. The hemodynamic variables were compared between groups, and were examined by correlation analysis. Regarding SVR, MSA patients exhibited a prolonged latency and less heart rate acceleration following inspiratory cough. Compared with the tilt table test, the elevation of heart rate upon SVR was positively correlated to the increase of heart rate after head-up tilt. The correlation analysis indicated that the magnitude of blood pressure drop from supine to upright was positively associated with the SVR latency but negatively correlated with the heart rate changes upon SVR. The present study demonstrated that blunted heart rate response might explain MSA's vulnerability to postural challenge. PWD may be used to predict cardiovascular response to orthostatic stress upon head-up tilt in MSA patients.